Pengembangan Buku Pendamping Bahan Ajar Tematik Kelas III SD/MI Berbasis Kearifan Lokal Daerah Kalimantan Barat - Mansur Mansur; Kartini Kartini (STKIP PGRI SITUBONDO, 2021)
This research is started from the lack of preparation of SD/MI Student Handbooks teaching materials that not represent the local wisdom of West Kalimantan. Therefore, this study aims to develop elements of local wisdom in teaching materials without having to eliminate the substance of the material that is the goal of the curriculum. The method used in this study is the Research and Development Model 4 D method, namely Define, Design, Development and Dissemination. Meanwhile, the instruments or data collection tools are documentation and Validation Questionnaire for the feasibility of the Companion Book that was developed. The result of this research is the compilation of 8 companion books for thematic learning based on Local Wisdom in West Kalimantan. for 4 Aspects of Assessment which include Assessment of Content Aspects of Materials the average aspect of the assessment is 4.68 equivalent to 93.75% with Valid / Eligible results for use, for aspects of Feasibility of presentation of subject matter in accordance with the Thematic Learning Book issued by the Ministry of National Education in 2018, the average assessment Expert Validator 4.76 is equivalent to a percentage of 95% with Valid / Eligible results for use. From the feasibility aspect of Book Design Display on the Development of Teaching Materials based on Local Wisdom of West Kalimantan class III for Theme 1 to Theme 8 4.8 from the expert validator assessment obtained an average value of 4.8 equivalent to a percentage of 96.7% with the criteria Valid / Eligible to use. As for the feasibility aspect of the language used in the development of teaching materials based on West Kalimantan local wisdom for class III for Themes 1 to 8, from the expert validator's assessment, an average value of 4.64 is equivalent to 96.7% which means valid / feasible to use.